Alignment of performance measurement to sustainability objectives: A variance-based framework - Dutta, Saurav; Lawson, R.; Marcinko, D. (Elsevier, 2013)
Meaningful incorporation of environmental and social responsibility goals into organizational strategic plans requires a mechanism to measure and reward performance contributing to that objective. This paper formulates such a framework using management accounting concepts. We demonstrate that the benefits of pursuing sustainability objectives can be decomposed into three parts. The first consists of what might be considered a natural outcome of pursuing the traditional economic goal of efficiency through cost-minimization (a "waste" variance). The second part consists of sustainability gains that produce societal benefit but may be incongruent with short-term economic goals (a "sustainability" variance). The third part stems from a change in optimal output level when that is considered endogenous to the firm (a "volume" variance). While elimination of waste variances can be encouraged using a traditional performance evaluation and reward structure, elimination of sustainability and volume variances requires redesign of performance evaluation tools and reward structures. We demonstrate that failure to recognize and incorporate the difference between the three variances can lead to inefficient allocation of resources, over- or under-production, and only partial fulfillment of environmental goals. Further, availability of shadow price information is essential to implementing such a performance measurement system; thus it is a public policy imperative to develop markets that establish such prices. © 2013 Elsevier Inc.